Hubungan Antara Gelombang Suara dan Pola Getaran Pada Benda Padat di Lingkungan - Margaretha, Maria; Kurniawati, Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to investigate the relationship between sound waves produced by solid objects and the vibration patterns induced in these objects. were carried out using various types of solid objects, including metal, wood, and plastic, which were subjected to various sources of sound vibrations with different frequencies. Measurements are carried out to record the sound waves produced and vibration patterns that occur in solid objects using vibration monitoring devices and microphones. The results showed a significant correlation between the characteristics of the detected sound waves and the vibration patterns observed in solid objects. Factors such as material composition, geometric shape, and intensity of the sound source influence the resulting vibration pattern. This discovery provides a better understanding of the interactions between sound waves and solid objects, which can have applications in a variety of fields including acoustic engineering, structural engineering, and sensor development. This study provides a basis for further research in understanding this phenomenon in more depth.